Production of Chitosan Oligosaccharides using β-glycosidic degrading enzyme: optimization using response surface methodology - Nurhayati, Yusof; Abd Manaf, Ali (Penerbit Universiti Sultan Zainal Abidin, 2020)
Many researchers have focused chitosan as a source of potential bioactive material during the past few decades. However, chitosan has several drawbacks to be utilised in biological applications, including poor solubility under physiological conditions. Therefore, a new interest has recently emerged on partially hydrolysed chitosan, chitosan oligosaccharides (COS). In this study, degradation of chitosan was performed by Cellulase from Trichoderma reesei® 1.5L and Response Surface Methodology (RSM) were employed to optimize the hydrolysis temperature, pH, enzyme concentration and substrate concentration. Optimization of cellulase T. reesei® using central composite design (CCD) was to obtain optimum parameters and all the factors showed significant effects (p˂0.05). The maximum response, Celluclast® activity (1.268 U) was obtained by assaying the process at 49.79oC, pH 4.5, 3% (v/w) of enzyme concentration and 25% (w/v) concentration of chitosan for 24 hours.